Clinical and molecular characterization of Korean children with infantile and late-onset Pompe disease: 10 years of experience with enzyme replacement therapy at a single center - Min-Sun Kim; Ari Song; Minji Im; June Huh; I-Seok Kang; Jinyoung Song; Aram Yang; Jinsup Kim; Eun-Kyung Kwon; Eu-Jin Choi; Sun-Ju Han; Hyung-Doo Park; et al. (Korean Pediatric Society, 2019)
Purpose Pompe disease (PD) is an autosomal recessive disorder caused by a deficiency of acid alphaglucosidase resulting from pathogenic GAA variants. This study describes the clinical features, genotypes, changes before and after enzyme replacement therapy (ERT), and long-term outcomes in patients with infantile-onset PD (IOPD) and late-onset PD (LOPD) at a tertiary medical center. Methods The medical records of 5 Korean patients (2 male, 3 female patients) diagnosed with PD between 2002 and 2013 at Samsung Medical Center in Seoul, Republic of Korea were retrospectively reviewed for data, including clinical and genetic characteristics at diagnosis and clinical course after ERT. Results Common initial symptoms included hypotonia, cyanosis, and tachycardia in patients with IOPD and limb girdle weakness in patients with LOPD. Electrocardiography at diagnosis revealed hypertrophic cardiomyopathy in all patients with IOPD who showed a stable disease course during a median follow-up period of 10 years. Patients with LOPD showed improved hepatomegaly and liver transaminase level after ERT. Conclusion As ERT is effective for treatment of PD, early identification of this disease is very important. Thus, patients with IOPD should be considered candidates for clinical trials of new drugs in the future.